Radioterapia no Câncer do Nasofaringe - Vieira, Antonio Pinto (2023)
Our experience with câncer of the nasopharynx is concerned with 87 cases examined and treated from 1939 to 1954. They were all confirmed by biopsy directly made from the nasopharynx. In this paper only 37 of the patients are considered, 33 of them belonging to the National Câncer Service and 4 from my private practice. They were seen during the period from 1939 to 1949, therefore having finished treatment for at least 5 years ago. The distribution of the cases according to the histological examination is the following: Transitional cell carcinoma: 20 cases, Squamous cell carcinoma: 11 cases, Reticulosarcoma: 3 cases, Lymphosarcoma: 3 cases. In all cases a radiological study of the nasopharynx, was made routinely with X-rays taken in lateral, Hirtz, fronto-nasal and mento-nasal positions being made. Radiological examination was of great value not only as a diagnostic means but also to show the frequent invasion of the base of the skull and also as a means of follow-up control. In our cases, 15 (40%) showed bone invasion at the base of the skull. Relation of cranial nerve invasion and bone destruction of the base of the skull was studied. Ten (27%) of our cases showed cranial nerve involvement. Câncer of the nasopharynx was treated exclusively by irradiation. Surgery was not employed for the following 3 reasons: 1rt) Difficult approach. 2nd) — Frequent bone invasion at the base of the skull which would made total extirpation impossible. 3d) — Most of the tumors are of the anaplastic type with distant lymph gland involvement. Treatment consisted exclusively in roentgentherapy, radium being also done associated by in 3 cases. Radiotherapy was done by the fractionated method, and the duration of treatment varied from 6 to 12 weeks. Physical factors were the following: kilovoltage varied from 200 to 400 Kv. Filtration was always 1.0mm. Cu. and the half value layer varied from 1.5 to 3.0mm. of Cu. The tumor dose varied from 3,000 to 6,000r. In all cases 4 fields were routinely given (2 lateral traszigomatical and 2 infra-orbitrarial). To treat the cervical node metastasis other fields were employed, always according to the size of the tumors. Six of the 37 cases were not treated due to their great advancement with lymph node, visceral and boné invasion. Five (167c) of the 31 cases treated, survived 5 and more years with no symptoms of cancer.